The use of unmanned aerial vehicles in agriculture - Юн, Г. М.; Мединський, Д.В. (Science-based technologies, 2017)
The article analyzes the use of unmanned aerial vehicles in agriculture to protect plants against diseases and pests by studying foreign experience in the use of mobile, airborne, complexes, marketing research of foreign companies and studying the advantages and disadvantage of UAV in comparison with manned aircraft. Certainly, that the use of unmanned aerial vehicles is widespread in many countries of the world, and the results of research in this direction despite the short period of introduction of this technology are presented by numerous scientific publications. The volume of the world market of unmanned aerial systems is constantly increasing, and Ukraine, taking into account the high development of the aircraft manufacturing industry, can become one of the leading manufactures of integrated solutions and services for the ever grooving needs of this market. Ukraine has the potential to use UAV in agriculture in terms of technical, economic, human resources . An analysis was conducted of the main UAV manufacturers in agriculture of foreign countries and Ukraine; the basic, technical characteristics of UAV are determined, in particular those used in agriculture; on the basis of which the SWOT analysis of the development of the strategy of unmanned agricultural aviation pin Ukraine is presented. The possibility of developing a strategy for the development of unmanned agricultural aviation in Ukraine is considered. Certainly , in order to effectively develop production and use of unmanned aerial vehicles, additional funding and development of programs is needed to direct the revitalization of the State in this direction(provision of benefits ,state support for the producer of technologies and services, development of programs for inform[in[g about technologies and manufacturers of to consumers in the field of agriculture, as well as the organization of training of personnel for the introduction of UAV in the agricultural needs of the population).